Reduced cortical thickness in World Trade Center responders with cognitive impairment. Issue 1 (13th July 2020) - Clouston, Sean A. P.; Deri, Yael; Horton, Megan; Tang, Cheuk; Diminich, Erica; DeLorenzo, Christine; Kritikos, Minos; Pellecchia, Alison C.; Santiago‐Michels, Stephanie; Carr, Melissa A.; Gandy, Samuel; Sano, Mary; et al.
Abstract: Introduction: This study examined cortical thickness (CTX) in World Trade Center (WTC) responders with cognitive impairment (CI). Methods: WTC responders (N = 99) with/without CI, recruited from an epidemiologic study, completed a T1‐MPRAGE protocol. CTX was automatically computed in 34 regions of interest. Region‐based and surface‐based morphometry examined CTX in CI versus unimpaired responders. CTX was automatically computed in 34 regions of interest. Region‐based measures were also compared to published norms. Results: Participants were 55.8 (SD = 0.52) years old; 48 had CI. Compared to unimpaired responders, global mean CTX was reduced in CI and across 21/34 cortical subregions. Surface‐based analyses revealed reduced CTX across frontal, temporal, and parietal lobes when adjusting for multiple comparisons. Both CI and unimpaired WTC groups had reduced CTX in the entorhinal and temporal cortices compared to published normative data. Discussion: Results from the first structural magnetic resonance imaging study in WTC responders identified reduced CTX consistent with a neurodegenerative disease of unknown etiology.